Comparison of frontal QRS-T angle in mitral valve prolapse without arrhythmic phenotype with healthy individuals - Celal Kilit (Medicine Science)
Mitral valve prolapse (MVP) is generally known as a benign disease with a good prognosis. Patients with the arrhythmic MVP (AMVP) phenotype have an increased risk of ventricular arrhythmia and sudden cardiac death. The frontal QRS-T angle is a new indicator, related to malign arrhythmias and cardiac death risk in various diseases. This study aimed to compare the frontal QRS-T angle of patients with MVP without the AMVP phenotype with that of healthy subjects. Fifty MVP patients without the AMVP phenotype, identified through a retrospective review of medical records, constituted the MVP group, and 50 healthy individuals constituted the control group. Frontal QRS-T angle and other electrocardiography and echocardiography parameters were compared between the groups. The groups were similar in terms of demographic characteristics and laboratory results. Frontal QRS-T angle was similar in both groups (30±37° vs 28±24°, p=0.56). There was also no difference in other electrocardiographic and echocardiographic parameters between the groups. In MVP patients without the AMVP phenotype, the frontal QRS-T angle does not change compared to healthy individuals. The risk of ventricular arrhythmia and sudden cardiac death in this patient population appears to be similar to that in healthy individuals. [Med-Science 2024; 13(4.000): 990-4]